2012
DOI: 10.4012/dmj.2011-216
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of dental ZrO<Sub>2</Sub>-based materials after hydrothermal fatigue. Part I: XRD, XRF, and FESEM analyses

Abstract: The aim was to investigate the effect of simulated low-temperature degradation (s-LTD) and hydrothermal fatigue on the degradation of three ZrO2-based dental materials. Lava, IPS, and NanoZr discs were randomly assigned to (1) Control-Storage in distilled water at 37°C; (2) Aging at 134°C for 5 h (s-LTD); (3) Thermocycling in saliva for 30,000 cycles (TF). XRD revealed that ZrO2 m phase was identified in all groups but TF increased the m phase only for Lava. Under the FESEM, Lava showed no alterations under s-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 37 publications
1
3
1
1
Order By: Relevance
“…In a study conducted by Perdigao et al, an increase in the monoclinic phase occurred after thermocycling. This difference can be due to higher thermal cycles and lower yttria content in the aforementioned study, compared to those reported for the current study [ 39 ].…”
Section: Discussioncontrasting
confidence: 66%
“…In a study conducted by Perdigao et al, an increase in the monoclinic phase occurred after thermocycling. This difference can be due to higher thermal cycles and lower yttria content in the aforementioned study, compared to those reported for the current study [ 39 ].…”
Section: Discussioncontrasting
confidence: 66%
“…In previous reports on the XRF of 3Y-TZP, 4Y-PSZ, and 5Y-PSZ, the primary elements were Zr, Y, and HF, and for Zr, the content concentration was almost the same as in the present study 41) . In addition, it was reported that 3Y-TZP did not show any change, as deduced by comparing the XRF results before and after LTD treatment 42) .…”
Section: Discussionmentioning
confidence: 90%
“…XRD analysis is not precise when the m-phase is less than 5%, and peak identification may be complicated by the background noise. 50 Therefore, the crystalline structure should also be analyzed by using Raman spectroscopy, which is more sensitive than XRD, 51 to…”
Section: Discussionmentioning
confidence: 99%